Tetrodotoxins Secretion and Voltage-Gated Sodium Channel Adaptation in the Ribbon Worm Kulikovia alborostrata (Takakura, 1898) (Nemertea) - Anna E. Vlasenko; Vasiliy G. Kuznetsov; Grigorii V. Malykin; Alexandra O. Pereverzeva; Peter V. Velansky; Konstantin V. Yakovlev; Timur Yu. Magarlamov (Toxins, 2021)
Nemertea is a phylum of marine worms whose members bear various toxins, including tetrodotoxin (TTX) and its analogues. Despite the more than 30 years of studying TTXs in nemerteans, many questions regarding their functions and the mechanisms ensuring their accumulation and usage remain unclear. In the nemertean Kulikovia alborostrata, we studied TTX and 5,6,11-trideoxyTTX concentrations in body extracts and in released mucus, as well as various aspects of the TTX-positive-cell excretion system and voltage-gated sodium (Nav1) channel subtype 1 mutations contributing to the toxins’ accumulation. For TTX detection, an immunohistological study with an anti-TTX antibody and HPLC-MS/MS were conducted. For Nav1 mutation searching, PCR amplification with specific primers, followed by Sanger sequencing, was used. The investigation revealed that, in response to an external stimulus, subepidermal TTX-positive cells released secretions actively to the body surface. The post-release toxin recovery in these cells was low for TTX and high for 5,6,11-trideoxyTTX in captivity. According to the data obtained, there is low probability of the targeted usage of TTX as a repellent, and targeted 5,6,11-trideoxyTTX secretion by TTX-bearing nemerteans was suggested as a possibility. The Sanger sequencing revealed identical sequences of the P-loop regions of Nav1 domains I–IV in all 17 studied individuals. Mutations comprising amino acid substitutions, probably contributing to nemertean channel resistance to TTX, were shown.